2021
DOI: 10.1103/physrevd.104.044002
|View full text |Cite
|
Sign up to set email alerts
|

Black hole scalarization with Gauss-Bonnet and Ricci scalar couplings

Abstract: Spontaneous scalarization is a gravitational phenomenon in which deviations from general relativity arise once a certain threshold in curvature is exceeded, while being entirely absent below that threshold. For black holes, scalarization is known to be triggered by a coupling between a scalar and the Gauss-Bonnet invariant. A coupling with the Ricci scalar, which can trigger scalarization in neutron stars, is instead known to not contribute to the onset of black hole scalarization, and has so far been largely … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 33 publications
3
25
0
Order By: Relevance
“…Instead of the linear nonminimal coupling of the form β 4 φR, we can also consider nonminimal couplings with higherorder powers, i.e., αµ 4 φ p R with p ≥ 2, besides the GB couplings [111]. As in the case of p = 1, the contributions to f and h from µ 4 appear at the order of j = 2, while the scalar-field derivative starts to receive corrections from the third order.…”
Section: Quartic and Gb Couplingsmentioning
confidence: 99%
“…Instead of the linear nonminimal coupling of the form β 4 φR, we can also consider nonminimal couplings with higherorder powers, i.e., αµ 4 φ p R with p ≥ 2, besides the GB couplings [111]. As in the case of p = 1, the contributions to f and h from µ 4 appear at the order of j = 2, while the scalar-field derivative starts to receive corrections from the third order.…”
Section: Quartic and Gb Couplingsmentioning
confidence: 99%
“…More broadly, the method introduced here can, in principle, also be used to calculate the sensitivities of black holes in other gravity theories, e.g., the effective field theory introduced in [21], the effective field theory for black hole scalarization of [90], the models of [107][108][109], and generalizations of ESGB gravity with multiple scalar fields [110]. Indeed, we expect the sensitivities, as calculated here, to play a role beyond ESGB theories: see Refs.…”
Section: Discussionmentioning
confidence: 78%
“…In a unified framework, we aim to investigate the dynamic aspects of both the scalarization and descalarization processes in isolated black holes. We explore the temporal evolutions closely related to their static counterpart in a scalarization model featured by the non-minimal couplings of a scalar field to the Gauss-Bonnet and Ricci scalar invariants, derived by Antoniou et al [30] recently. In particular, we elaborate on four distinct scenarios for which the gravitational systems are typically far from equilibrium.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…In particular, we elaborate on four distinct scenarios for which the gravitational systems are typically far from equilibrium. In [30], the authors showed that there exists a (rescaled) mass threshold around 1.18. If the mass of the spacetime is below this threshold value, scalarization is triggered by scalar perturbations without any node, and the corresponding static black hole metric is characterized by a non-trivial scalar field outside its horizon.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%